Suspension development for a prototype Urban Personal Vehicle - Abyzov, Sergej (My University, 2014)
This thesis describes the process of suspension development for a prototype Urban Personal Vehicle (PUNCH). The PUNCH is a crash safe prototype of an Urban Personal Vehicle developed at the Chalmers University of Technology, Gothenburg, Sweden. The urban personal vehicle is designed for the dense urban areas of today. It's a small, car-like vehicle with space for one driver (and maybe one or two passengers) that is to be driven at city speeds (sub 50 [km/h]). It needs to be nimble and easy to drive. The thesis starts by defining the requirements for this vehicle, limitations of project and the iterative process of suspension design. Thereafter the literature study is presented in the theory chapter. After that, the selection of design and parts is shown, design draft is made and analysed in a whole vehicle simulation computer programme. From the simulation results conclusions are made and recommendations for the physical fabrication and future work are given. The finished concept is a double wishbone suspension font and rear. The suspension has a predictable character without any sudden changes. The suspension characteristics are as close as possible to the given targets, but for some limitation due to packaging issues presented by the already existing frame. The suspension front and rear share many components, so the final design requires less unique manufacturing (at a later phase/future work). Some components (as brake assembly, wheel hubs & bearings) are taken straight from a common road car (simple, cheap, off the shelf components). The ride is predicted to be comfortable without too much roll during cornering.
Keywords: Farkostteknik; Transport; Vehicle Engineering; Transport